1998
DOI: 10.1007/s004360050467
|View full text |Cite
|
Sign up to set email alerts
|

Murine schistosomiasis mansoni: experimental analysis of bone marrow and peripheral myelopoiesis

Abstract: In schistosomiasis a systemic hyperplasia of the monomacrophagic cell lineage is associated with its mild modifications in myelograms and hemograms. We monitored the in vitro proliferation of myeloid precursors obtained from bone marrow, blood, spleen, and liver. The macrophage colony-forming unit (M-CFU) numbers were stable in bone marrow but increased progressively in spleen and in liver, reaching in each organ the values equivalent to one femur. The bone marrow had an increased production and enhanced capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Many studies have demonstrated that MDSC play key roles in the inhibition of anti-tumor immunity [22][24] through a variety of mechanisms including nutrient starvation [25], the generation of reactive oxygen and nitrogen species (ROS and RNOS) [26], [27], and the induction of regulatory T cells [28], [29]. There are few reports of MDSC in parasitic infections, such as Schistosoma [30][32], Leishmania donaovani [33], [34], and Toxoplasma gondii [35][37]. However, the MDSC-like cells in Schistosoma mansoni or Leishmania donaovani infections have not been well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that MDSC play key roles in the inhibition of anti-tumor immunity [22][24] through a variety of mechanisms including nutrient starvation [25], the generation of reactive oxygen and nitrogen species (ROS and RNOS) [26], [27], and the induction of regulatory T cells [28], [29]. There are few reports of MDSC in parasitic infections, such as Schistosoma [30][32], Leishmania donaovani [33], [34], and Toxoplasma gondii [35][37]. However, the MDSC-like cells in Schistosoma mansoni or Leishmania donaovani infections have not been well defined.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the kinetics of granuloma formation, we performed morphometry in lesions at three different time points (6, 8 and 12 weeks after infection), corresponding to the early and late acute phases, and to the early chronic phase of this process, respectively (Dutra et al, 1998). The dynamics of granuloma formation depends on the assembly of various types of cells, their in situ proliferation, and on the generation of connective tissue matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the helminth Schistosoma mansoni was shown to increase the number of bone marrow GM-CFU during the acute infection phase -correlating with increased M-CSF (or CSF-1) and IL-3 levels -which then return to normal levels during the chronic phase [26,27]. Interestingly, the extramedullary myelopoiesis in spleen and liver gradually increases throughout the course of infection [28]. An intriguing observation is the presence of high levels of GM-CFU in the liver granulomas (higher than in femurs) during the chronic infection phase, which are locally supported by GM-CSF and cell membrane-associated proteoglycans [26,29,30].…”
mentioning
confidence: 99%